Population genetic analysis of oceanic paddle crab (Varuna litterata) in Thailand - Juthamas Suppapan,; Jamjun Pechsiri,; Sompong O-Thong,; Arunrat Vanichanon,; Pradit Sangthong,; Verakiat Supmee, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Population genetic structure of Varuna litterata living along the coast of Thailand were examined in this study. The samples were collected from 3 coastal regions: The Andaman sea (Satun, Trang, Phang Nga), the lower Gulf of Thailand (Pattani, Songkhla, Nakhon Si Thammarat) and the upper Gulf of Thailand (Petchburi, Samut Songkram, Rayong, Trat). Intraspecific variation was determined based on partial sequences of the cytochrome oxidase subunits I gene. A total of 182 samples were collected but only 32 haplotypes were obtained from these samples. An excess of rare haplotypes indicated that the female effective population size of V. litterata living along the coast of Thailand is large. Estimated values of haplotype diversity and nucleotide diversity were 0.790 and 0.003, respectively. The AMOVA (analysis of molecular variance) and phylogenetic analysis results showed that based on genetic variation, the population of this organism was found to have 2 genetically different populations: The Andaman sea population and the Gulf of Thailand population. Genetic exchange of V. litterata among populations inhabiting along the coast of Thailand could be described by the stepping stone model. The results of neutrality tests, both Tajima’s D and Fu’s Fs statistics, yielded negative values (-1.992 and -26.877, respectively) and statistically significant deviation from the neutrality, indicating that the V. litterata living along the Thailand coast had experienced population expansion. Mismatch distribution analysis indicated that a possible expansion occurred 211,428 years ago during the Pleistocene glaciations period.